Television News Violence and Children’s Fear Reaction - Wang, Lin (2005)
Do parents perceive that exposure to violence on television news programs is a problem for their young children? Although considerable research has shown that media violence in other forms (cartoons, movies, television entertainment programs) has several negative effects on children, almost no research or policy attention has been given to children’s exposure to violent events in television news broadcasts. The purpose of this study was to examine the rates of 4-5 years old children’s exposure and fear reaction to television news violence as it relates to several ecological variables, including parental gender, race, education level, household income, family structure and family composition, parents’ concern and parental behavior regarding television news violence. General perceptions of television news violence and observations of their children’s exposure and fear reaction to television news were collected from 27 parents from 4 childcare centers in Knoxville. This project indicates that an ecological approach is a feasible way to examine children’s television news consumption and their reactions. The findings revealed that television news violence has already become an issue about which some parents express general concern. However, the rates of 4-5 year old children’s exposure to television news and their fear reactions are actually not high. In addition to exploring parental attitudes about and actions in regards to television news viewing by their young children, a second question explored the parents’ comparison between television news and children’s cartoons in term of media violence. On one hand, parents seemed to believe that television news is more concerned about violence in television news than in children’s cartoons; on the other hand, parents’ actual limitation of children’s exposure to these two programs was almost the same, and fewer parents reported their child experienced fear to television news than to children’s cartoons